Mujer cisgénero en situación de trabajo sexual: “nos ven como el foco infeccioso o como el virus andante” - Perdomo Sandoval, Luis Albeiro; Villamil Camacho, Diego Fernando (Index de Enfermeria, 2023)
Objective: To explore the perceived barriers to sexual health self-care of a 57year-old cisgender woman in sex worker situation. Methods: A biographical account of a qualitative, constructivist and phenomenological nature was addressed. Results: From the systematic and content analysis, the following themes emerged: sex work as a life alternative; stigma and discrimination due to occupational identity; the lack of preventive, humanized and inclusive health care; the necessary self-esteem to care for oneself; informal psychology as a method of screening the client; professional knowledge in protective and care practices; gaps and difficulties in the use of the male condom; and the need for a public policy with a gender and inclusive perspective. Conclusions: The narrative reflects the need to address the barriers to sexual health self-care, through participatory and inclusive methodologies that promote the cooperation of preventive health policies, strategies, and interventions consistent with the needs of female sex workers.
Cisgender woman in a situation of sex work: “they see us as the infectious focus or as the walking virus”
Keywords: public policy; self-care; sex worker; sexual health; social discrimination; social vulnerability; Scopus